DAMPAK BEBAN KERJA, STRES KERJA, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING DI UPT. PUSKESMAS KENDIT SITUBONDO (PADA KARYAWAN NON ASN) - Putri, Dewi Rahmawati; Hamdun, Edy Kusnadi; Anshory, Muhammad Iqbal (Fakultas Ekonomi dan Bisnis, 2024)
Puskesmas or (Public Health Center) is one of the government agencies engaged in public health. The function of the Puskesmas or (Public Health Center) is as a health center for health development in the region. This study aimed to analyze and test the impact of workload, work stress and work environment on job satisfaction through motivation as an intervening variable in health centers. Work Environment on Job Satisfaction through Motivation as an Intervening Variable in UPT. Kendit Situbondo Health Center (On Non-State Civil Apparatus). The population in this study is all Non-State Civil apparatuses at UPT. Kendit Health Center Situbondo has a population of 50 employees with sampling using a saturated sampling technique, meaning it is taken as a whole. The analysis in this study used the help of the Smart PLS 3.0 application. The results of hypothesis testing in direct influence using the Smart PLS 3.0 application show that workload has a significant positive effect on work motivation, work stress has a significant positive effect on work motivation, work environment has a significant positive effect on work motivation, workload has a negative insignificant effect on job satisfaction, work stress has a negative insignificant effect on job satisfaction, work environment has a positive insignificant effect on job satisfaction, work motivation has a positive insignificant effect on job satisfaction through work motivation, work stress has a positive insignificant effect on job satisfaction through work motivation, and work environment has a positive insignificant effect on job satisfaction through work motivation.